Coordinating Biointeraction and Bioreaction of a Nanocarrier Material and an Anticancer Drug to Overcome Membrane Rigidity and Target Mitochondria in Multidrug‐Resistant Cancer Cells. (12th May 2017) - Zhang, Rui Xue; Li, Lily Yi; Li, Jason; Xu, Zhensong; Abbasi, Azhar Z.; Lin, Lucy; Amini, Mohammad A.; Weng, Wei Yu; Sun, Yu; Rauth, Andrew M.; Wu, Xiao Yu
Abstract: Multidrug resistance (MDR) is a main cause of chemotherapy failure in cancer treatment. It is associated with complex cellular and molecular mechanisms including overexpression of drug efflux transporters, increased membrane rigidity, and impaired apoptosis. Numerous efforts have been made to overcome efflux transporter‐mediated MDR using nanotechnology‐based approaches. However, these approaches fail to surmount plasma membrane rigidity that attenuates drug penetration and nanoparticle endocytosis. Here, a "one‐two punch" nanoparticle approach is proposed to coordinate intracellular biointeraction and bioreaction of a nanocarrier material docosahexaenoic acid (DHA) and an anticancer prodrug mitomycin C (MMC) to enhance mitochondrion‐targeted toxicity. Incorporation of DHA in solid polymer‐lipid nanoparticles first reduces the membrane rigidity in live cancer cells thereby increasing nanoparticle cellular uptake and MMC accumulation. Subsequent intracellular MMC bioreduction produces free radicals that in turn react with adjacent DHA inducing significantly elevated mitochondrial lipid peroxidation, leading to irreversible damage to mitochondria. Preferential tumor accumulation of the nanoparticles and the synergistic anticancer cytotoxicity remarkably inhibit tumor growth and prolonged host survival without any systemic toxicity in an orthotopic MDR breast tumor model. This work suggests that combinatorial use of biophysical and biochemical properties of nanocarrier materials with bioreactive prodrugs is a powerful approach to overcoming multifactorial MDR in cancer. Abstract : A nanocomposite of binary lipids and polymer with anticancer prodrug mitomycin C (MMC) (MMC‐DHA‐PLN) is designed to overcome multifaceted drug resistance. It first utilizes the biointeraction of nanomaterial docosahexaenoic acid (DHA) to facilitate cellular uptake of the nanoparticle‐encapsulated MMC, and then synchronizes intracellular activation of MMC and lipid peroxidation of DHA to damage mitochondria, leading to enhanced anticancer efficacy in vitro and in vivo.